Tales From the Crypt: The Expanding Role of Slow Cycling Intestinal Stem Cells - Carlone, Diana L. (2012)
Similar to other highly self-renewing tissues, the intestinal epithelium contains both slowly and rapidly cycling progenitor/stem cells, though their relationship has been largely unexplored. Two recent reports in Nature (Tian et al., 2011) and Science (Takeda et al., 2011) shed new light on their dynamic interplay.